Hallmarks of Bone Metastasis - Johnson, Rachelle W. (Calcif Tissue Int, 2017)
Breast cancer bone metastasis develops as the result of a series of complex interactions between tumor cells, bone marrow cells, and resident bone cells. The net effect of these interactions are the disruption of normal bone homeostasis, often with significantly increased osteoclast and osteoblast activity, which has provided a rational target for controlling tumor progression, with little or no emphasis on tumor eradication. Indeed, the clinical course of metastatic breast cancer is relatively long, with patients likely to experience sequential skeletal-related events (SREs), often over lengthy periods of time, even up to decades. These SREs include bone pain, fractures, and spinal cord compression, all of which may profoundly impair a patient’s quality-of-life. Our understanding of the contributions of the host bone and bone marrow cells to the control of tumor progression has grown over the years, yet the focus of virtually all available treatments remains on the control of resident bone cells, primarily osteoclasts. In this perspective, our focus is to move away from the current emphasis on the control of bone cells and focus our attention on the hallmarks of bone metastatic tumor cells and how these differ from primary tumor cells and normal host cells. In our opinion, there remains a largely unmet medical need to develop and utilize therapies that impede metastatic tumor cells while sparing normal host bone and bone marrow cells. This perspective examines the impact of metastatic tumor cells on the bone microenvironment and proposes potential new directions for uncovering the important mechanisms driving metastatic progression in bone based on the hallmarks of bone metastasis.